2021
DOI: 10.1111/inm.12894
|View full text |Cite
|
Sign up to set email alerts
|

Deciding to discontinue prescribed psychotropic medication: A qualitative study of service users’ experiences

Abstract: Many mental health service users decide to discontinue their psychotropic medication at some stage in the treatment process; however, few studies have captured these experiences. This study aimed to explore people’s experiences of coming off medication. A qualitative descriptive design and individual interviews with 23 people who experienced coming off medication were employed. COREQ checklist was used. Data were analysed using inductive and deductive approaches and six major themes were developed. Findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…This is attributable to individuals' unique experiences of BZRA use (e.g., reasons for initiating and maintaining BZRA use) and the range of barriers that can impact on individuals attempting discontinuation of long‐term BZRA use 16 . This is consistent with previous research on mental health service users' experiences of discontinuing psychotropic medication 32 . The collection of BCTs within the toolkit offers a library of options for individuals and clinicians to use as part of an active partnership in developing a gradual dosage reduction strategy that should include regular monitoring and support.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This is attributable to individuals' unique experiences of BZRA use (e.g., reasons for initiating and maintaining BZRA use) and the range of barriers that can impact on individuals attempting discontinuation of long‐term BZRA use 16 . This is consistent with previous research on mental health service users' experiences of discontinuing psychotropic medication 32 . The collection of BCTs within the toolkit offers a library of options for individuals and clinicians to use as part of an active partnership in developing a gradual dosage reduction strategy that should include regular monitoring and support.…”
Section: Discussionsupporting
confidence: 85%
“… 16 This is consistent with previous research on mental health service users' experiences of discontinuing psychotropic medication. 32 The collection of BCTs within the toolkit offers a library of options for individuals and clinicians to use as part of an active partnership in developing a gradual dosage reduction strategy that should include regular monitoring and support. The retrospective coding of interventions in our previous systematic review 12 identified a comparatively smaller repertoire of BCTs, whereby the number of BCTs per intervention ranged between 4 and 8 BCTs and 17 unique BCTs were identified across included studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some service users decide to discontinue psychotropic medication to recapture lost personal autonomy, to live a life free of medication and, in some cases, because these medications have failed to manage the person's distressful experience and symptoms 18 . However, these individuals have reported challenges in accessing professional support and having their autonomy and choice respected 18,19 .…”
Section: Psychotropic Medications Have Various Adverse Effectsmentioning
confidence: 99%